Nilai Pendidikan Agama Islam dalam Bersosial Media pada Mahasiswa UHAMKA Jakarta - Setyowati, Dwi; Hariyati, Farida; Ariska, Cynthia (Jurnal Pendidikan Islam, 2025)
This study aims to examine how the values of Islamic Religious Education are reflected in the behavior of students of Universitas Muhammadiyah Prof. Dr. HAMKA (UHAMKA) when doing activities on social media. This research uses a qualitative approach with in-depth interviews with six active students from various faculties who consciously and actively use social media. The results showed that UHAMKA students make social media not only as a means of communication and entertainment, but also as a space for learning, sharing kindness, and building personal branding by prioritizing Islamic ethics and values. They are accustomed to applying the principle of tabayun (verification of information), maintaining digital communication ethics, and balancing the use of social media with worship obligations. The values of Islamic education that are internalized through formal learning and campus religious activities have proven to play an important role in shaping awareness of social media in a healthy, responsible manner, and oriented towards the benefits of the world and the hereafter.